Bedřich Loewenstein’s Theory of Civilisation - Calta, Jan (Dějiny – teorie – kritika, 2016)
Research on the foundations and the spirit of modern Western civilisation and civic society is one of the main fields of interest of the Czech philosopher and historian Bedřich Loewenstein. In his studies Loewenstein defends European liberal and rationalist, enlightened traditions. Inspired by Norbert Elias’s notion of civilisation process, he views civilisation as a sublimation of instinctive human life, a state in which a normative, supra-group element comes to dominate the inner nature of individuals. He sees civilisation as a precondition of progress, since in the form of ‘presence of the non-present’, it preserves and maintains historically older elements and formations in the present life. It is also a game (cf. Huizinga’s notion of Homo ludens), which requires some generally respected rules and a plurality of game partners and situations. He emphasises its dialogical nature, which – while taking into account the relativity of its own perspective – does not seek to overturn diverging positions regarding values and interests, but engages them in communication and tries to stimulate self-reflection. Loewenstein investigates the process of civilisation shortcuts which aid the transmission of past experiences through norms and knowledge, and pays attention to the process of rationalisation. And finally, Loewenstein views civilisation as a constantly re-established balance between the particular areas of life. Civilisation is thus not a given, immutable state, but an evolving, dynamic process.